(untitled) (Jornal Memorial da Medicina, 2021)
Idiopathic Lumbosacral Plexitis is a disease that do not have definitive causes but even starts to be studied by Sander Evans et al. in 1981 hypotheses were put forward related to viral infections, vaccines and heterologous serum. Although more recently studies have showed that the disease can develop without immunological history. Multiple roots and nerves are affected and it can be bilateral. The diferential diagnosis of other pathologies must involves research for tumours, traumas and diabetes. The findings of the disease include: autoimmune demyelination and vasculitis with axonal lesion. The clinicalconditionare characterized by intensive pain, paresis, hypoesthesia in lower members, and a limping gait. The prognosis is positive, however do not have a completely remission without squeals. The treatment has not been defined but is common to uses corticosteroids and immunoglobulin.